Senųjų žemdirbystės laukų tyrinėjimai šiaurės vakarų Lietuvoje - Merkevičius, Algimantas; Nemickienė, Rėda (Archaeologia Lituana, 2003)
The emergence and development of farming is one of the main archaeological problems.The development stage of farming is displayed by the fossil fields distributed all over Lithuania. They are signified by stone cairns, stone walls and baulks, mostly preserved in forests situated close to water bodies. Many of these sites were destroyed during the Land Reform and land amelioration carried out during the soviet times. Even today, demolition of cairns and stone baulks continues, as forests are felled, arable lands expand and stones are gathered for building activities. The majority of fossil fields have survived in north-western Lithuania, Kretinga and Skuodas districts.Investigation of the old fossil fields provides information about the size of these fields, the territories they occupy, their types and the cultures which were cultivated. These sites are of key importance as regards reconstruction of the early economic system, the settlement network and even the model of the social structure of the society.In Lithuania, investigations of fossil fields started right before the Second World War and since then have been conducted until today with quite long interruptions.The present article surveys the investigation stages of fossil fields in north-western Lithuania, the main problems, specificity and the most important sites which were investigated.Investigations of the ancient fields can be divided into three main stages.Stage I started in the late thirties and ended in the beginning of the eighties of the 20th century. During this stage, more than 20 of these objects were found and described. Some of these were measured, and small-scale archaeological excavations were conducted in a number of sites. At that time the function of these objects was not conceived yet. They were considered to be either burial or other archaeological sites of obscure function.Stage II started in the beginning of the eighties and ended in late nineties of the 20th century. In the beginning of this stage the function of these objects was established and publicised. Small-scale archaeological excavations were carried out as well.Stage III started in late nineties of the 20th century. During this stage, international and interdisciplinary investigations of fossil fields were launched. A number of new fossil fields were found, some of which were situated close to other archaeological sites. Consequently, archaeological complexes were defined.In the thirties of the 20th century Ignas Jablonskis was the first to draw attention to stone cairns and baulks. He first noticed cairns in 1938 in the communal pastures of Tauzai village (Skuodas district). That same year I. Jablonskis informed the Cultural Museum of Vytautas the Great about a “cremation cemetery” found at Tauzai. In his letter he writes that one grave was uncovered and charcoal with ashes were found in the depth of about 0.5 m, including the grave paving. That same year I. Jablonskis mapped the Tauzai stone cairns. He identified the cairns as burial mounds. In 1939 I. Jablonskis found three further sites of this type in Padvariai, Kluonaliai and Šlaveitai. That same year he measured the fossil fields at Padvariai and Budriai. He used a theodolite to draft the plans. In 1939 I. Jablonskis published an article in “Lietuvos aidas” which voiced concern over devastation of archaeological sites, including the objects under consideration.Before the war, in the late thirties and the beginning of the forties a Land Reform was carried out and farmers were intensively preparing land lots for cultivation which resulted in destruction of archaeological sites. With a view to preservation or at least documentation of these sites, I. Jablonskis wrote letters to the Cultural Museum of Vytautas the Great informing about the matter. The Museum administration was not indifferent to the problem. Director of the Museum P. Galaunė appealed to the Governor of Kretinga County regarding measuring and protection of the sites. Worker of the Museum Pranas Baleniūnas was sent out to western Lithuania. From 1939 to 1941 he conducted archaeological investigations in the area. Along with other archaeological sites found and described in his report were stone cairns, most commonly located in communal pastures of a number of villages. He interpreted cairns as burial mounds or “just some monuments”. He carried out small-scale archaeological excavations at some of these sites. In 1939 P. Baleniūnas excavated 4 stone cairns in the communal pastures of Tauzai. During the excavations no other finds apart from charcoal were recovered. In 1940 he excavated 5 cairns at the village of Medšarkė and found charcoal as weil as burnt clay. The largest number, i. e. 10 cairns, excavated by P. Baleniūnas were located at Erlėnai. These were constructed from stones of different size. P. Baleniūnas noticed that they had the same structure with a big stone in the centre, covered up with smaller stones of different size. No other finds apart from charcoal were found. The data about cairns presented by P. Baleniūnas is particularly important as most of them were completely destroyed or badly demolished soon after.Before the Second World War, in the process of destruction of cairns and baulks farmers most often found charcoal, though other finds also occurred. A stone axe was found during destruction of a stone baulk in Padvariai. A further stone axe was found together with charcoal under a cairn in the area of Padvariai. Stone axes were also found in other fossil fields such as Kluonaliai and Tinteliai.After the War, in 1948, the Institute of History organized the first archaeological survey which included examination of stone cairns. One cairn was investigated at the village of Tauzai. No archaeological finds were recovered. As no archaeological finds, except charcoal, were being recovered, the interest in these sites faded. After the War, I. Jablonskis was the only one researcher who continued prospecting, surveying. investigation and mapping of these sites in northwestern Lithuania. He was gathering data about the ancient fields though he did not yet realise their function. In 1964 and 1965 I. Jablonskis found cairns at Kašučiai village (Kretinga District), dose to the Kašučiai lake. They were situated in three large groups on the eastern side of the lake. He mapped these later on. In 1980 I. Jablonskis found the Kašučiai cairns, baulks and stone walls. In 1981 he mapped them and excavated one cairn, namely cairn 12. It is located on the left bank of the Akmena River, in the forest of Kašučiai village. During the survey and excavation of Auksūdis Kūliai mound in 1974, he found cairns as weil. According to I. Jablonskis, there were cairns both inside and outside the mound. They were especially numerous in the western part of the Pilalė forest. I. Jablonskis offered a hypothesis that the Kūliai mound was a prehistoric fortified settlement and the cairns were related to it.The end of the first investigation stage and the beginning of the second stage are associated with the clarification of the functions of cairns and baulks. In 1976–1978, during amelioration of fields in Padvariai village, on the left bank of the Akmena River, “a partly burnt rod paving along with surviving cairns and baulks” were found. When I. Jablonskis found this site, he realised that cairns and baulks signified the places of early fanning. He was the first to give a correct interpretation of these objects. In his report of 1981 I. Jablonskis presented data on a number of fossil fields and for the first time dearly articulated that cairns and baulks were remnants of the early agricultural fields. He published these conclusions in the “Mokslas ir gyvenimas” (Science and Life) journal in 1983. As the function of these objects was established, the second investigation stage commenced. This stage is mostly associated with the name of I. Jablonskis as weil. A number of new objects were found during this stage as weil, some of these were excavated and mapped. Isolated articles were published with references to cairns as unquestionable remnants of the ancient agricultural fields. In 1986 I. Jablonskis excavated the Senkai cemetery (Kretinga district) and found a cairn in its territory. Its northern part was investigated. During excavations a layer of sizeable charcoal was found in the depth of 0.5 m.At the end of stage II, in the nineties, fossil fields attracted the interest of the Department of Archaeology of Vilnius University. Literature on the subject was gathered, including Lithuanian, Estonian and Scandinavian publications. During visits to Sweden archaeological sites of the type were examined together with other objects. In the late nineties a decision was made to conduct archaeological investigations of the ancient fields. In 1999 a group of students from the Department of Archaeology of Vilnius University, accompanied by Head of the Division of History of Kretinga Museum and directed by Algimantas Merkevičius made a study trip to Kretinga during which the archaeological sites located in the district were examined. During the excursion fossil fields were also surveyed. The Kašučiai fossil fields were once again surveyed in November 2000 together with Estonian archaeologists Marge Konsa and Valter Lang, who has been investigating such sites in his country for about 10 years. It was then that a decision was made to carry out joint archaeological investigations of these objects with participation of Vilnius and Tartu Universities and Kretinga Museum. The investigations started in spring 2001. Fossil fields in Kretinga and Skuodas districts were surveyed, the Kašučiai cairns and stone walls were excavated and mapped. On the latter site, a trench measuring 6 x 2 m was excavated across the stone wall. The excavations revealed that the wall had been 6m wide and 0.50–0.53 m high. Excavations at the wall yielded 4 silver coins, Dutch thalers, which have nothing to do with the construction of the wall. The expedition of Vilnius and Tartu Universities, and Kretinga museum continued investigations of the fossil fields in autumn 2001. At that time mapping and excavation of the Kašučiai cairns and baulks, located dose to the Kašučiai lake, started. A trench of 5 x 1 m was excavated here across one baulk. The excavations established that the baulk had been 3.7 m wide and up to 0.47 m high. The investigation and mapping of this site continued in spring 2002 during the third international expedition of the institutions mentioned above. At that time a new site was found and mapped, i. e. the Padvariai fossil fields, situated about 300 m eastwards of the left bank of the Akmena River, in a small forest. These fields are quite regular, mostly rectangular in shape, encircled with stone and earth baulks. In archaeological literature they are called the Celtic fields.In autumn 2001, the Department of Archaeology of Vilnius University in association with the Institute of Geology and Geography, and the Museum of Kretinga prepared a project on “The Early Agricultural Field Systems in Western Lithuania” which was submitted to the Lithuanian State Science and Studies Fund. In spring 2002 the Fund assigned financing for the realization of the project. In 2002 the international investigations of the ancient fields in northwestern Lithuania developed into interdisciplinary investigations. In June 2002, thanks to the financial support from the Lithuanian State Science and Studies Fund, archaeological excavations were launched at the fossil fields found and mapped at Padvariai earlier that spring. During these investigations, a trench of 20 sq m was excavated across one of the baulks. It was established that the baulk had been 5.5 m wide. Charcoal was found under the baulk and submitted for radiocarbon dating.In March and September 2002 the executors of the project collected data on fossil fields in Estonia and Sweden respectively. Some fossil fields were surveyed.On 8–9 October 2002 the third international conference “In Honour of Jonas Puzinas” was arranged in Vilnius. A paper on “Investigation of fossil fields in Lithuania” was delivered at the conference. In the second half of October that year, the Department of Archaeology of Vilnius University in association with Kretinga Museum surveyed the fossil fields in Kretinga and Skuodas districts. Researchers from the Institute of Geology and Geography took part in the expedition as well. They took samples for further macro and micro botanical analysis from the boggy lake of Kašučiai. During the expedition most of the ancient fields mentioned in archaeological sources were surveyed. In almost all the fields cairns, stone walls and baulks were found, though reports indicate that these objects had been demolished. During the survey, fossil fields not mentioned in archaeological sources were also found, including Senkai, Tūbausiai (Kretinga district) and others. The discovered remains of fields were commonly located in forests.The ancient fields were indisputably an integral part of settlements in the broad sense. Arable fields and pastures were set up close to settlements. Burial sites, hillforts and settlements as well as fossil fields have been found in northwestern Lithuania, but they were isolated objects. After the last archaeological field walking expedition in autumn 2002, a number of complex archaeological sites, comprising settlements, burial sites and fossil fields were defined.Complex and interdisciplinary investigations will establish the chronological framework of separate field types and their relationship with other archaeological objects, as well as other issues related to this subject.